PENGARUH KUALITAS PELAYANAN(SERVICE QUALITY) TERHADAP KEPUASAN NASABAH (CUSTOMER SATISFACTION) DI PT. BPRS MITRA MANDIRI SUKSES DI GRESIK - Rokhmat Subagiyo (Universitas Muhammadiyah Sidoarjo, 2016)
Objectives of this research are: (1) to determine the variables of service quality (tangible, reliability, responsibility, assurance, and empathy) significantly simultaneously (together) on customer satisfaction at PT. BPRS Mitra Mandiri Success in Gresik; (2) determine the variables of service quality (tangible, reliability, responsibility, assurance, and empathy) significantly partially (in part) on customer satisfaction at PT. BPRS Mitra Mandiri Success in Gresik and (3) determine the variables of service quality (tangible, reliability, responsibility, assurance, and empathy) are the dominant influence on customer satisfaction at PT. BPRS Mitra Mandiri Success in Gresik.